A Case of Intraoperative Reproducible Transient Bradycardia During Total Hip Arthroplasty: Direct Activation of Parasympathetic Vagal Afferents From Bone - Yifan Li; Joseph Moskal; Maxine Lee (Case Reports in Anesthesiology)
The Gallagher–Wilkinson reflex was first reported by Gallagher and Wilkinson in 2001, describing intraoperative transient and reproducible bradycardia and/or asystole during intramedullary reaming in patients undergoing total knee replacement. The reflex has been originally thought to result from an indirect mechanism: the elevated intramedullary pressure transmits to intrapelvic and intra-abdominal viscera, indirectly causing a vagally mediated reflex bradycardia. Other case reports have documented this reflex and discounted potential physiologic causes such as microemboli or primary cardiac arrhythmia. Several preclinical and clinical studies have demonstrated how the parasympathetic innervation of bone modulates bone remodeling. This paper presents a case of a patient who underwent a total hip replacement, experiencing intraoperative transient and reproducible bradycardia. We postulate a direct mechanism for the Gallagher–Wilkinson reflex: increased pressure from intramedullary reaming directly activates the parasympathetic nervous system in the bone axis leading to vagally-mediated bradycardia. This case offers an alternative explanation for the Gallagher–Wilkinson reflex and emphasizes the important need for additional research to better understand parasympathetic innervation in the bone axis.